Final answer:
To prove the given statement a ar ar² ⋯ ar^(n−1) = a(1−r^n)/(1−r) using induction, we need to show that the base case holds and then prove the statement for the inductive step.
Step-by-step explanation:
To prove the given statement using induction, we will follow the steps provided.
a) Base case: n = 1;
When n = 1, the equation becomes: a = a(1-r^1)/(1-r). This is true, so the base case holds.
b) Inductive step: Assume true for n = k;
Assume that the statement is true for n = k, which means: a ar ar^2 ... ar^(k-1) = a(1 - r^k)/(1 - r).
c) Prove for n = k+1;
To prove for n = k+1, we need to show that: a ar ar^2 ... ar^(k-1) ar^k = a(1 - r^(k+1))/(1 - r).
d) Prove for n = k-1;
To prove for n = k-1, we need to show that: a ar ar^2 ... ar^(k-1) = a(1 - r^(k-1))/(1 - r).